The impact of benthic microbial communities in sediment dispersion and bedform preservation: a view from the oldest microbially induced sedimentary structures in South America - Warren, Lucas Veríssimo [UNESP]; Varejão, Filipe Giovanini; Quaglio, Fernanda; Inglez, Lucas [UNESP]; Buchi, Fernanda [UNESP]; Simões, Marcello Guimarães [UNESP] (FapUNIFESP (SciELO), 2021)
The influence of microbial communities upon sedimentary dynamics is an issue of increasing significance. Over the last decades, studies have revealed a particular class of sedimentary structures and textures produced by the interaction among distinct flows, marine substrate, and benthic microbial communities. We present evidence of the oldest record of microbially-induced sedimentary structures (MISS) in South America, as recorded in low-grade metasedimentary rocks of the Early Mesoproterozoic (~1536 ± 33 Ma) Tiradentes Formation, state of Minas Gerais, SW Brazil. Types 1, 2, and 3 correspond to wrinkle, pustular, and dome structures related to flat or rippled bed surfaces, preserved in metasandstone deposited in shallow marine settings. Evidence supporting the microbial origin of these structures includes delicate morphology, degree of alignment, presence of original mat cover, and orientation of quartz grains indicating biostabilization. The presence of distinct MISS associated with well-preserved ripple marks, wrinkled surfaces, and flatbeds suggests deposition under varied energy conditions with different potentials for the preservation of surficial structures. Vertical growth of microbial communities influences sediment cohesion and stability. This reduces substrate roughness and, as a consequence, wave and current shear, thereby increasing the preservation potential of bedforms and delicate features of their bedding surfaces.
Keywords: Marine transitional settings; Mesoproterozoic; Microbially-induced sedimentary structures; MISS morphogenesis; Siliciclastic rocks